2012
DOI: 10.1109/tmi.2011.2173766
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three MRI-Based Anatomical Priors for Quantitative PET Brain Imaging

Abstract: In emission tomography, image reconstruction and therefore also tracer development and diagnosis may benefit from the use of anatomical side information obtained with other imaging modalities in the same subject, as it helps to correct for the partial volume effect. One way to implement this, is to use the anatomical image for defining the a priori distribution in a maximum-a-posteriori (MAP) reconstruction algorithm. In this contribution, we use the PET-SORTEO Monte Carlo simulator to evaluate the quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
136
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 30 publications
1
136
0
1
Order By: Relevance
“…21 such as a negative mutual information or negative joint entropy [49,53,110]. A recent study showed that Bowsher prior-based image reconstruction [109] yielded the best image quality among edge information-based method, region-based method, and joint entropy-based method [52]. Iterative image reconstruction requires evaluating the gradient of regularizers at every (sub-)iterations, so computation complexity for using anatomical information-based regularizers is high.…”
Section: Anatomical Information For Noise Reduction Mathematical Modementioning
confidence: 99%
See 1 more Smart Citation
“…21 such as a negative mutual information or negative joint entropy [49,53,110]. A recent study showed that Bowsher prior-based image reconstruction [109] yielded the best image quality among edge information-based method, region-based method, and joint entropy-based method [52]. Iterative image reconstruction requires evaluating the gradient of regularizers at every (sub-)iterations, so computation complexity for using anatomical information-based regularizers is high.…”
Section: Anatomical Information For Noise Reduction Mathematical Modementioning
confidence: 99%
“…Ideas of using structural couplings between molecular and anatomical images for reconstruction have been studied a couple of decades ago [41][42][43]. Recently, interesting advances for noise reduction of molecular images using anatomical information have been introduced with state-of-the-art methods for post-reconstruction filtering [44][45][46][47] or regularization in inverse problems [48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, an improvement in one figure of merit does not imply an improvement of all possible figures of merit (8). To suppress noise and Gibbs artifacts, resolution modeling is best combined with the use of anatomical prior information during, e.g., a maximum a posteriori (MAP) image reconstruction (9). In addition, detection accuracy of hypometabolic regions can be significantly improved in this way (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Given this ill-posed problem of PET image reconstruction with low-count projection data, in the maximum likelihood (ML) PET reconstruction framework, penalised likelihood (PL) reconstruction (or equivalently maximum a posteriori, MAP ) has been extensively studied [1][2][3][4][5][6][7]. Such methods involve adding a regularisation (penalty) term to the log likelihood function, and thus the effective forward model complexity can be controlled by changing the weight of this regularisation.…”
mentioning
confidence: 99%
“…Among the penalty models, anatomical images acquired by high-resolution magnetic resonance (MR) or X-ray computed tomography (CT) from the same subject are considered useful, as they provide the prior information on the underlying structures. Recent reviews on using anatomical prior information for PET image reconstruction can be found in [5,6,10], and the Bowsher method [4] which encourages PET image smoothness over the neighbour voxels selected from the anatomical image, was found to achieve better performance while being relatively efficient computationally compared to other methods [5]. Apart from the penalised likelihood PET reconstruction frameworks, very recently an alternative perspective of using the image-derived prior was proposed in [11], by incorporating the prior information into the image representation via kernel functions, and the regularisation was applied to the PET forward model.…”
mentioning
confidence: 99%